Serum plasminogen as a potential biomarker for the effects of low-dose benzene exposure. (1st December 2018) - Liang, Boxuan; Zhong, Yizhou; Chen, Kengkeng; Zeng, Lihai; Li, Guoliang; Zheng, Jiewei; Jiang, Liang; Xie, Zhiwei; Que, Bingling; Lai, Guanchao; Wu, Banghua; Yang, Xingfen; et al.
Highlights: Serum PLG level increases in low-dose benzene exposure workers. Serum PLG levels are positively correlated with benzene exposure levels. Serum PLG level was higher in WBC abnormal benzene exposure workers. Abstract: Exposure to low-dose benzene may lead to hematotoxicity and cause health problems. Though peripheral blood cell count is widely used in benzene exposure assessment and health risk assessment, the reports regarding the effects of low-dose benzene exposure on blood cell count remain inconsistent. To uncover more sensitive biomarkers for low-dose benzene exposure, our previous study screened out three potential serum proteins—plasminogen (PLG), platelet basic protein (PBP) and apolipoprotein B100 (ApoB100)—as biomarkers from chronic benzene poisoning patients by using proteomic analysis. In the present study, we verify the three serum proteins as biomarkers for the effects of low-dose benzene exposure in a large low-dose benzene exposure population. The study showed that serum PLG increased in benzene exposed workers and was positively correlated with benzene exposure levels. However, no significant changes in serum PBP or ApoB100 were found in the benzene exposed workers. To explore whether the candidate serum proteins are associated with hematotoxicity, the study population was regrouped into two groups, based on their WBC counts. Our results showed that the workers with high serum PLG levels suffered higher risk of WBC abnormalities than did workers with low serum PLG levels. Taken together, these findings indicate that the increase in serum PLG might be associated with low-dose benzene exposure and benzene–induced hematotoxicity. Thus, we suggest serum PLG could be used as a potential biomarker for the effects of low-dose benzene exposure.